PERFORMANCE-BASED EVALUATION OF THE BAKAUHENI â TERBANGGI BESAR TOLL ROAD BRIDGE BASED ON SNI 1725:2016 AND SNI 2833:2016 (CASE STUDY : IC TERBANGGI BESAR BRIDGE) - Dendi Nosya, Akhmad
There are many structural systems that can be chosen in building a bridge. One of them is the prestressed concrete bridge system. An example of the use of a bridge with prestressed concrete construction is the IC Terbanggi Besar Bridge STA. 139+925, which is a bridge located on the Bakauheni – Terbanggi Besar toll road in Lampung Province. The IC Terbanggi Besar Bridge was completed in 2018, but it was designed before 2016, so an evaluation of the current code is needed to determine the performance of the bridge and determine the repair method if there is a potential for failure.. This research aims to review the design planning of prestressed concrete bridges using the MIDAS Civil software. The structure is modeled with the working loads such as Dead Load (DL), Super Imposed Dead Load (SIDL) and earthquake load according to the new loading regulations SNI 1725:2016 and earthquake loading SNI 2833:2016. This study evaluates the application of the Non-Linear Time History Analysis Method on the bridge based on the design parameters described in the NCHRP 440 and 949 documents with the help of Midas Civil software. These documents summarize the design parameters in the form of concrete material strength, steel reinforcement, and drift that occurs in the lateral resisting elements (bridge piers) which are composed of reinforced concrete material so that it can be identified as the limit of structural damage to the bridge after an earthquake to determine the structural performance. The analysis is carried out using 7 pairs of ground motions that represent the conditions at the bridge location to evaluate the design criteria based on the bridge performance category. The results of this study show that the performance level of the IC Terbanggi Besar Bridge structure is at the fully operational performance level..